HUBUNGAN PERAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM PEMENUHAN AKTIVITAS SEHARI-HARI DI PUSKESMAS BELIMBING PADANG - Abri Madoni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In Indonesia, the elderly who experience limitations in carrying out physical activity every year have increased. The dependence of the elderly turns out to have an effect on the affective function of the family which includes love, mutual acceptance, mutual respect and the bond of living together with all family members. The purpose of this study is the relationship between the role of the family and the independence of the elderly in fulfilling daily activities at the Belimbingpadang Health Center in 2021. This type of research is descriptive analytic with a cross sectional study design. The study was conducted in October 2020 - November 2021. The elderly population who came to visit the Belimbing Padang Health Center was 530 people with a sample of 77 people. The sampling technique is accidental sampling. Data analysis was performed by univariate analysis presented with frequency distribution and bivariate analysis using Chi-Square statistical test with 95% confidence level = 0.05. The results showed that more than half (53.2%) of the elderly had a poor family role at the Belimbing Padang Health Center. More than half (54.5%) of respondents have independent dependence at the Belimbing Padang Health Center. There is a significant relationship between the role of the family and the independence of the elderly in fulfilling daily activities at the Belimbing Padang Health Center. It is hoped that through the leadership of the Belimbing Padang Health Center in order to be able to run the elderly program about health education, fulfilling daily activities in the elderly, and providing information to the family to provide support, attention and enthusiasm for the elderly. Keywords: Family Role, Elderly Independence, Daily activities